Robust monetary policy with the cost channel - Tillmann, Peter; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
Recent research argues that model uncertainty leads the central bank to adjust interest rates stronger to exogenous disturbances than under certainty. This paper investigates whether the introduction of a cost channel of monetary transmission, whose presence is empirically supported, changes the impact of model uncertainty on interest rate setting. The basic model is simple enough to facilitate an analytical closed form solution. We find that the presence of the cost channel dampens the effect of model uncertainty on interest rate setting and can even offset the activist policy stance. In this case, the conventional result is reversed and uncertainty induces an attenuated interest rate policy. A richer dynamic model corroborates these findings.
Economic Papers